Complication of venovenous extracorporeal membrane oxygenation cannulation – the significance of an inferior vena cava anomaly. Issue 12 (24th October 2016) - Yeung Ng, Pauline; Wong, Chiu Cheuk Alfred; Young, Karl; Kwong, Yin‐Yee; Sin, Wai‐Ching
Key Clinical Message: Physicians should be aware of possible anatomical variants during cannulation for extracorporeal membrane oxygenation (ECMO). Particular attention to ensure continual visualization of the guidewire before proceeding to final positioning of the ECMO cannulae should be paid. Alternative imaging modalities should be contemplated when uncertainties arise to minimize the risk of inadvertent vascular injuries. Abstract : Physicians should be aware of possible anatomical variants during cannulation for extracorporeal membrane oxygenation (ECMO). Particular attention to ensure continual visualization of the guidewire before proceeding to final positioning of the ECMO cannulae should be paid. Alternative imaging modalities should be contemplated when uncertainties arise to minimize the risk of inadvertent vascular injuries.